2017
DOI: 10.3390/met7040148
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Corrosion Behavior of Mechanically-Alloyed Cu–Zr–Ti Bulk Metallic Glasses

Abstract: Cu 60 Zr 30 Ti 10 metallic glass powder was prepared by mechanically alloying a mixture of pure Cu, Zr, and Ti powders after 5 h of milling. Cu 60 Zr 30 Ti 10 bulk metallic glass (BMG) was synthesized by vacuum hot pressing the as-milled Cu 60 Zr 30 Ti 10 metallic glass powder at 746 K in the pressure range of 0.72-1.20 GPa, and the structure was analyzed through X-ray diffraction and transmission electron microscopy. The pressure could enhance the thermal stability, and prolong the existence, of the amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…(a) Cu-based alloys are not oxidized if they contain at least Ti. It is connected with good protective properties of the surface films containing both Ti and Zr oxides [31,32]. However, the binary Zr50Cu50 ( Figure 4) and ternary Cu60Zr30V10 (Figure 2b) alloys are severely oxidized.…”
Section: Alloymentioning
confidence: 94%
“…(a) Cu-based alloys are not oxidized if they contain at least Ti. It is connected with good protective properties of the surface films containing both Ti and Zr oxides [31,32]. However, the binary Zr50Cu50 ( Figure 4) and ternary Cu60Zr30V10 (Figure 2b) alloys are severely oxidized.…”
Section: Alloymentioning
confidence: 94%
“…Since the discovery of bulk metallic glasses (BMGs), they have been receiving attention from researchers because of their excellent properties, such as high strength and a high corrosion resistance [ 1 , 2 , 3 , 4 , 5 ]. In particular, Cu-based BMGs have been the focus of research due to their high glass-forming capacity and thermal stability [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Ti-Cu-Zr-Ni system was known to form amorphous alloys (or metallic glasses) [21]. Many materials scientists established various rules in order to improve the amorphous forming ability of the Ti-Cu-Zr-Ni system [22]. Zhai et al reported that the addition of Sn into the Ti-Cu-Zr-Ni system could promote the amorphous forming ability of the composite alloys [23].…”
Section: Introductionmentioning
confidence: 99%